Is team unity a predictor of athletes` competitive motivation? - Yamada, K. (The Japan Journal of Coaching Studies, 2019)
Majority of athletes spend their competitive careers as sports team members and share time with other teammates. It is an essential practice for sport coaches to build team relationships. Team unity is one index for assessing these conditions. Therefore, it was hypothesized that team unity would facilitate the athletes' performance. This study examined whether team unity predicts athlete's competitive motivation as a major contributory factor of performance, and whether collective efficacy and sports commitment mediate the relationship between team unity and competitive motivation in Japanese athletes. Data were collected via questionnaires; 957 athletes from 43 sports participated in this study. The questionnaire included four scales assessing psychological variables: the Unity Scale for Sports Teams, the Volition for Competition Scale, the Psychological Performance Collective Efficacy Scale, and the Sport Commitment Scale. The results showed significant positive correlation between team unity, competitive motivation, collective efficacy, and sport commitment. Covariance structure analysis showed that team unity indirectly predicted competitive motivation, and both collective efficacy and sport commitment were mediators for the relationship between team unity and competitive motivation regardless of athlete's gender, sport types, or roles within the team. Results indicated that team unity was positively related to competitive motivation. Furthermore, although enhancing team unity did not directly improve athletes' competitive motivation, it would indirectly improve competitive motivation. Collective efficacy and sports commitment were particularly helpful in facilitating the competitive motivation of athletes. These findings suggested that coaches and athletes should attend to team psychological factors including unity for developing sports performance.